Influence of spatial confinements on the group velicities of acoustic phonons in PbI2 nanofilms - Lutsiuk, Yuriy; Kramar, Valeriy (Research and Publishing Center of the Shevchenko Scientific Society, 2022)
Result of theoretical study the group velocities of acousstic phonon in the quasi-2D nanosystem such us the flat ultr-thin fillms of lead iodide crystal.
Keywords: acoustic phonons, group velosity, lead iodide, nanofilm